AXIOLOGY OF YOGA IN THE SCRIPTURE OF GHERANDA SAMHITA - I Gusti Made Widya Sena; Ida Bagus Putu Adnyana; I Komang Suastika Arimbawa (UHN I Gusti Bagus Sugriwa Denpasar, 2025)
The background of this research is that apart from interpreting the verses related to God and yoga practice contextually, it also aims to analyze the axiology of yoga in the Gheranda Samhita scripture so that the knowledge obtained by academics and yoga practitioners is more comprehensive. Axiology in terms of terms is a study related to the theory of value or the study of everything that can be valuable or provide benefits. One scripture that can be used as a reference to get the value or benefits of yoga is the Gheranda Samhita. Through qualitative descriptive methods, using hermeneutic theory, this research found the following findings: First, Yoga ethics as described in the Gheranda Samhita scripture; Second, Seven exercise as a form of seven yoga practises; Third, Ahara yoga as a form of healthy food consumption; Fourth, Asana, as a body form in doing yoga by doing 32 asana poses; Fifth, Mudra, is another term for the mystical movements of the two hands; Sixth, Pratyahara-Pranayama and Seventh, Dhyana-Samadhi. These seven axiological values of yoga are found in the Gheranda Samhita scripture to help a person achieve physical fitness, mental balance and spiritual awareness.